Pelatihan Pengelolaan Limbah Cair Rumah Tangga pada Masyarakat Pesisir : Pelatihan Pengelolaan Limbah Cair Rumah Tangga pada Masyarakat Pesisir - islam, fahrul; Ahmad, Haeranah; Saddania, Sitti (Jurnal Pengabdian Kesehatan Komunitas, 2024)
Sanitation is an important factor in public health, including coastal communities. One of the environmental health problems in Indonesian society, including coastal communities, is family latrines which can have a negative impact on people's health status. The aim of this service is to increase the knowledge and skills of Coastal Communities regarding household liquid waste management. The target of this service activity is the people of Babana Pantai Hamlet who often defecate on the beach as many as 20 people. The service methods used are health education and demonstrations. The service activity stages began with education about stopping open defecation, then continued with a Demonstration about how to make a Drumpicon (Drum Ipal Concentrate) and finally education on household liquid waste management. Participants were very enthusiastic about taking part in the activity as indicated by their timely attendance and activeness in asking questions. Service results: after education, 90% of participants had good knowledge about stopping open defecation and 85% of participants had good knowledge about managing household liquid waste. A model Drumpicon was formed in one of the residents' houses which is expected to motivate other households not to defecate in the openSanitation is an important factor in public health, including coastal communities. One of the environmental health problems in Indonesian society, including coastal communities, is family latrines which can have a negative impact on people's health status. The aim of this service is to increase the knowledge and skills of Coastal Communities regarding household liquid waste management. The target of this service activity is the people of Babana Pantai Hamlet who often defecate on the beach as many as 20 people. The service methods used are health education and demonstrations. The service activity stages began with education about stopping open defecation, then continued with a Demonstration about how to make a Drumpicon (Drum Ipal Concentrate) and finally education on household liquid waste management. Participants were very enthusiastic about taking part in the activity as indicated by their timely attendance and activeness in asking questions. Service results: after education, 90% of participants had good knowledge about stopping open defecation and 85% of participants had good knowledge about managing household liquid waste. A model Drumpicon was formed in one of the residents' houses which is expected to motivate other households not to defecate in the open.   Abstrak Sanitasi merupakan faktor penting dalam kesehatan masyarakat tidak terkecuali bagi masyarakat pesisir. Salah satu masalah dalam kesehatan lingkungan pada masyarakat Indonesia termasuk pada masyarakat pesisir adalah jamban keluarga yang dapat berdampak buruk pada status kesehatan masyarakat. Tujuan pengabdian ini adalah untuk meningkatkan pengetahuan dan keterampilan Masyarakat Pesisir tentang pengelolaan limbah cair rumah tangga. Sasaran kegiatan pengabdian ini yaitu masyarakat Dusun Babana Pantai yang sering Buang Air Besar di pantai sebanyak 20 orang. Metode pengabdian yang digunakan adalah Ceramah Tanya Jawab dan Demonstrasi. Tahapan kegiatan pengabdian dimulai dengan edukasi tentang stop buang air besar sembarangan, kemudian dilanjutkan dengan Demonstrasi Pembuatan Drumpicon (Drum Ipal Consentrat) dan yang terakhir adalah edukasi pengelolaan limbah cair rumah tangga. Peserta sangat bersemangat mengikuti kegiatan yang ditandai dengan kehadiran peserta tepat waktu dan keaktifan dalam memberikan pertanyaan. Hasil pengabdian: setelah dilakukan edukasi,  90% peserta memiliki pengetahuan yang baik tentang stop buang air besar sembarangan dan 85% peserta memiliki pengetahuan yang baik tentang pengelolaan limbah cair rumah tangga. Terbentuk 1 Drumpicon percontohan di salah satu rumah warga yang diharapkan dapat memotivasi rumah tangga yang lain untuk tidak buang air besar sembarangan.